Giving back: making research results relevant to local groups and conservation - Shanley, P.; Laird, S.A. (Routledge, 2002)
Information generated by researchers to formulate policy and planning often remains in the domain of policy makers, academics and researchers, conceptually and geograhically distant from the region of study. Furthermore, governments and conservation organizations frequently make or promote land use decisions without fully informing or involving the local communities most affected. This article describes several case studies in which making research results available to local people held numerous conservation and development advantages, and improved project impact.